Розпізнавання зображень за допомогою цифрових фільтрів з модифікованими імпульсними характеристиками - Капустій, Б.О.; Надобко, О.В.; Репік, В.М. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
General conception of recognition of images with noises using nonrecursive digital filters is formed. The scheme of algorithm of correlated image recognition is proposed. The influence of recognition system parameters on the authentication of true identification of image with etalon is investigated.